OA unpaid#21699 Pregnant Women’s Knowledge and Awareness of Sexually Transmitted Infections in Selected Public Health Facilities in the North West Province - Simônd Croesér Steenekamp; Khumoetsile Daphney Shopo (Africa Journal of Nursing and Midwifery, 2026)
Background: South Africa is considered to have a high prevalence of sexually transmitted infections (STIs), which continue to impose a major public health burden. Untreated STIs can lead to long-term, irreversible and potentially fatal outcomes in pregnant women. This study aimed to assess the knowledge and awareness of pregnant women in the North West Province (NWP) regarding STIs. Methods: A quantitative cross-sectional descriptive design was applied to reach the objective. Five health facilities were selected within one district in the NWP. A self-administered 58-item questionnaire was administered to 151 (n = 151) pregnant women and a 100% response rate was achieved. Data were analysed through inferential and descriptive statistics. Results: The mean knowledge for respondents in this study was 28.35 out of 50 questions. HIV was the most well-known type of STI and trichomoniasis, chlamydia and hepatitis B were the least known. The respondents had the least knowledge regarding transmission of STIs through breastfeeding. Only 21.9% of respondents were aware that STIs could be asymptomatic. Approximately 62.3% of respondents did not know that some STIs could be prevented through vaccination. Conclusion: There is poor knowledge regarding types of STI and more awareness strategies by health professionals are needed. Socio-demographic aspects was a major contributing factor to the poor knowledge regarding the types of STI and method of transmission.